GelMA hydrogel dual photo-crosslinking to dynamically modulate ECM stiffness - Smits, Josephina J. H. M.; van der Pol, Atze; Goumans, Marie José; Bouten, Carlijn V. C.; Jorba, Ignasi (Frontiers in Bioengineering and Biotechnology, 2024)
The dynamic nature of the extracellular matrix (ECM), particularly its stiffness, plays a pivotal role in cellular behavior, especially after myocardial infarction (MI), where cardiac fibroblasts (cFbs) are key in ECM remodeling. This study explores the effects of dynamic stiffness changes on cFb activation and ECM production, addressing a gap in understanding the dynamics of ECM stiffness and their impact on cellular behavior.Utilizing gelatin methacrylate (GelMA) hydrogels, we developed a model to dynamically alter the stiffness of cFb environment through a two-step photocrosslinking process. By inducing a quiescent state in cFbs with a TGF-β inhibitor, we ensured the direct observation of cFbs-responses to the engineered mechanical environment. Our findings demonstrate that the mechanical history of substrates significantly influences cFb activation and ECM-related gene expression. Cells that were initially cultured for 24h on the soft substrate remained more quiescent when the hydrogel was stiffened compared to cells cultured directly to a stiff static substrate. This underscores the importance of past mechanical history in cellular behavior. The present study offers new insights into the role of ECM stiffness changes in regulating cellular behavior, with significant implications for understanding tissue remodeling processes, such as in post-MI scenarios.